5. How Does Frailty Impact the Efficacy, Reactogenicity, Immunogenicity and Safety of the Adjuvanted Recombinant Zoster Vaccine? A Secondary Analysis of the ZOE-50 and ZOE-70 Studies. (31st December 2020) - Andrew, Melissa K; Kim, Joon Hyung; Matthews, Sean; Dessart, Christophe; levin, myron J; Oostvogels, Lidia; Riley, Megan; Schmader, Kenneth E; McNeil, Shelly; Schuind, Anne; Curran, Desmond
Abstract: Background: Herpes zoster can negatively impact older adults' health and quality of life. An adjuvanted recombinant zoster vaccine (RZV) has excellent vaccine efficacy (VE), including in older adults. Given that frailty is strongly associated with vulnerability to illness and adverse health outcomes, we studied how frailty impacts RZV VE, immunogenicity, reactogenicity, and safety. Methods: In the ZOE-50 and ZOE-70 pivotal Phase 3 efficacy studies of RZV, 29, 305 participants aged 50–96 received 2 doses of RZV vs. placebo in 1:1 randomization. In this secondary analysis (NCT03563183), a baseline frailty index (FI) was created retrospectively following previously validated methods using pre-existing comorbidities and patient reported outcomes. Participants were categorized as non-frail (FI≤ 0.08), pre-frail (FI=0.08–0.25) or frail (FI≥ 0.25) for stratified analyses. Results: FI was calculated for 99.8% of participants included in this secondary analysis (n=26, 976), and was balanced between RZV and placebo groups. 45.6% were pre-frail and 11.3% were frail. Mean age was 68.8 years; 58.1% were women. RZV VE against HZ was consistently above 90% for all frailty categories [non-frail: 95.8% (95%CI: 91.6–98.2), pre-frail: 90.4% (84.4–94.4), frail: 90.2% (75.4–97.0)]. The RZV group demonstrated robust antibody responses post-dose 2 across frailty categories. In the RZV group, the percentage of participants reporting solicited adverse events decreased with increasing frailty. Unsolicited medically attended visits and serious adverse events increased with frailty and were balanced between placebo and RZV groups. Conclusion: The ZOE studies included older adults who were frail and pre-frail, and VE was high across frailty categories. Reactogenicity decreased with increasing frailty, and no safety concerns were identified in any frailty group. Disclosures: Melissa K. Andrew, MD, PhD, MSc(Ph ), GSK (Grant/Research Support, Research Grant or Support) Joon Hyung Kim, MD, GSK (Employee, Shareholder) Sean Matthews, MSc, GSK (Consultant) Christophe Dessart, MSc, GSK (Employee) myron J. levin, MD, Curevo (Advisor or Review Panel member)GlaxoSmithKline (Grant/Research Support, Advisor or Review Panel member)GlaxoSmithKline (Grant/Research Support, Advisor or Review Panel member)Merck Research Laboratories (Advisor or Review Panel member, GlaxoSmithKline)Merck Research Laboratories (Advisor or Review Panel member)Merck ResearchLaboratories (Advisor or Review Panel member) Lidia Oostvogels, MD, GSK (Shareholder) Megan Riley, PhD, GSK (Employee) Shelly McNeil, FRCPC, MD, GSK (Grant/Research Support, Scientific Research Study Investigator, Research Grant or Support, Other Financial or Material Support, honoraria for talks) Anne Schuind, MD, GSK (Employee, Other Financial or Material Support, own GSK stock options or restricted shares as part of renumeration) Desmond Curran, PhD, GSK (Employee, Shareholder)